Neuraxial labor analgesia: a focused narrative review of the 2017 literature. Issue 3 (June 2018) - Kocarev, Mitko; Khalid, Fouzia; Khatoon, Fatima; Fernando, Roshan
Abstract : Purpose of review: Neuraxial labor analgesia remains the most effective and one of the most commonly utilized methods for pain relief during labor. This narrative review article is a summary of the literature published in 2017 on neuraxial analgesia for labor. Recent findings: From a total of 41 identified articles, 13 were included in the review. The topics have been structured into three categories: initiation of neuraxial analgesia, maintenance of neuraxial analgesia, and neuraxial analgesia and obstetric outcomes. Maintenance regimens, such as program intermittent epidural bolus (PIEB) techniques, remain a focus of extensive research with the potential to optimize analgesia for each individual patient. In a similar way, the dural puncture epidural technique could improve the quality of labor analgesia with fewer side effects compared with standard epidural and combined spinal epidural (CSE) techniques. Finally, the increased use of modern technology using portable ultrasound devices with automated imaging software to facilitate epidural catheter placement may offer potential advantages to the obstetric anesthesiologist, especially when dealing with technically difficult cases. Summary: Recent advances, as well as refinements, of current neuraxial analgesia techniques could improve women's experience of labor.